Pemanfaatan Media Audio Visual Youtube Untuk Meningkatkan Kemampuan Menulis Berita Pada Pembelajaran Indonesia - Fitria Dwi Widiastuti; Diena San Fauziya (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This research is motivated by the use of YouTube audio-visual media in improving the ability to write news for Indonesian language learning. Factor This research aims to determine the effectiveness of using YouTube audio-visual media in improving students' ability to write news and find out the challenges and obstacles in using YouTube audio-visual media. This research uses a qualitative-descriptive approach to collect data and information through the library study method. The results of this study show that the use of YouTube audio-visual media in learning Indonesian has great potential to improve students' news writing skills. The effectiveness of using YouTube as a learning tool can be seen from various aspects, including student involvement, increased understanding of concepts, and practical skills in writing news.